Determining working characteristics of the excess air pressure system in an emergency hatch based on jet water-gas ejectors - Hrynchak, Serhii (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is jet water and gas ejectors in the fire safety system of ships. The problem solved relates to the fact that in the event of a fire in the area of the exit from the ship's emergency room, the heat energy increases dangerously and a large amount of smoke spreads throughout the ship's rooms. These factors require immediate sealing of the emergency room, which limits the immediate access of emergency teams to the room. Installation of a local excess air pressure system in the emergency hatch on the basis of jet water and gas ejectors could make it possible to shield thermal energy and localize smoke gases in the emergency room without sealing it to ensure prompt access of emergency teams to it. The following results were achieved – the adequacy of theoretical studies of the processes of localization of flue gases in the emergency room without its sealing was confirmed by the experimental method. The investigated problem was solved by optimizing processes: the rate of change in the natural indicator of the weakening of environment during the start-up of the local excess air pressure system in the emergency hatch based on jet water and gas ejectors; the effectiveness of reducing the temperature of heated gases in the superstructure during the operation of the excess air pressure system in the emergency hatch based on jet water-gas ejectors. Special feature of the results was the formation of an air curtain obtained by the selection of a part of high-temperature flue gases in the housings of jet water-gas ejectors, their heat-mass exchange processing and output back into the flow. This created conditions under which thermal energy is shielded with an efficiency of 85–88 %. The scope and conditions of practical use of the results are shipbuilding and ship fire safety design